Air quality levels in the industrial city of Jubail, Saudi Arabia - AlQahtani, Abdullah I.; Salama, Khaled F.; Alwadei, Manna M.; Aljassim, Mohammed T.; Alsaif, Abdulmalik Salman; Al-Warthan, Mohammed; AlMulla, Abdulaziz A. (Frontiers in Environmental Engineering, 2024)
Ambient air quality remains a significant health and environmental challenge in developing cities, primarily due to the increasing gas emissions from fossil fuel use. Harmful outdoor air pollutants is a critical environmental and public health concern because poor air quality directly impacts human health, leading to respiratory and cardiovascular diseases. This study aimed to assess ambient gaseous air pollutants specifically sulfur dioxide (SO2), nitric oxide (NO), nitrogen dioxide (NO2), carbon monoxide (CO), and NMHC in Jubail Industrial City, Saudi Arabia.Hourly fixed-site air quality monitoring data were collected from three air quality monitoring stations distributed throughout the industrial city of Jubail, covering the period from January 2020 to December 2022. Beside the recorded hourly meteorological conditions. Standard monitoring equipment was used to observe pollutant concentrations at all three locations in Jubail. Notably, the highest emissions of CO, SO2, and NMHC occurred in 2021, while the highest emissions of NO, NO2, and NOx were recorded in 2022 with 2022 generally exhibiting the highest gas emissions and 2020 showing the lowest. Variations in gaseous contaminants were noted, influenced by changes in meteorological conditions and human activities. However, the levels of gaseous emissions remained within acceptable limits according to the air quality index. As a result, policies implemented during and after the COVID-19 lockdown successfully reduced the accumulation of gaseous emissions to below harmful levels, and it is crucial to maintain these measures moving forward.